An Empirical Case Study of Housing Mobility in Corporate Relocations: Equity Constraints and Corporate Incentives. Issue 1 (31st December 2022) - Alexandrova, Svetoslava; Reichert, Alan; Robinson, Spenser
Abstract: Using proprietary data from a large corporate relocation firm covering 2004–2014, this empirical case study examines the effects of housing equity, corporate relocation incentives, as well as economic, geographic, and demographic factors on employee mobility within the relocation framework. The corporate relocation dataset largely controls for potentially endogenous employment factors related to mobility. Consistent with previous studies the results indicate that low or negative home equity positions represent a statistically significant disincentive to employee mobility. Corporate moving incentives such as home sale guarantees, where the employer guarantees a sale at market or relocation appraised value, demonstrate a strong positive impact towards employees' willingness to accept a relocation offer. Results also reveal independence between the effects of constrained equity disincentives and corporate moving incentives; corporate moving incentives equally impact an equity constrained homeowner and a normal equity homeowner. Furthermore, macroeconomic, geographic, and regional differences have a moderate impact on the relocation decision. In terms of demographics, gender has little direct effect, while employees with families appear more willing to accept employment transfers.